The cabal - Hagberg, David (Hagberg, David. Kirk McGarvey adventures., 2010)
"CIA operative Todd Van Buren meets with a Washington Post investigative reporter who has uncovered strong evidence that a powerful lobbyist has formed a shadowy group called the Friday Club. The cabal's members include high-ranking men inside the government: a White House advisor, a three star general at the Pentagon, deputy secretaries at the State Department, Homeland Security, the FBI, and even the CIA. The reporter is convinced that the Friday Club is powerful enough to potentially topple the United States government...and he's terrified of what he knows. That afternoon, Van Buren--son-in-law to the legendary spy Kirk McGarvey--is gunned down. That evening, the reporter and his family are killed. All traces of the existence of the Friday Club are erased. A devastated McGarvey is soon drawn into the most far-reaching and dangerous investigation of his career, the stakes of which could destabilize the United States government, and shake the foundations of the world financial order."--Dust cover flap.